2017
DOI: 10.3892/mmr.2017.6251
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin protects against contrast-induced nephropathy via anti-apoptosis by the upregulation of Hsp27 in vivo and in vitro

Abstract: Contrast-induced nephropathy (CIN) is an iatrogenic acute renal failure occurring following the intravascular injection of iodinated radiographic contrast medium. However, the regulatory mechanisms for CIN remain to be fully elucidated. The present study aimed to investigate whether atorvastatin protects against CIN via anti-apoptotic effects by the upregulation of Hsp27 in vivo and in vitro. To determine whether atorvastatin attenuated CIN, the inflammatory response and apoptosis in vivo and in vitro, a rat m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Several regimens, such as N-acetylcysteine (NAC; a reactive oxygen scavenger), ascorbic acid, tocopherol, and atorvastatin, have been evaluated for reducing reactive oxygen species (ROS) levels to prevent CIAKI [ 24 27 ]. However, the preventive effects have been equivocal in many clinical studies [ 28 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several regimens, such as N-acetylcysteine (NAC; a reactive oxygen scavenger), ascorbic acid, tocopherol, and atorvastatin, have been evaluated for reducing reactive oxygen species (ROS) levels to prevent CIAKI [ 24 27 ]. However, the preventive effects have been equivocal in many clinical studies [ 28 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing Bax, caspase-3 protein levels and decreasing Bcl-2, HSP70 protein levels by western. [ 63 ] LLC-PK1 (Pig renal tubular epithelial cells) Iodixanol (Visipaque) 4.7-75 mgI/ ml 2h , 24h 1. Decreasing cell proliferation by MTT assay.…”
Section: In-vitro Studies On Contrast-induced Nephropathy (Cmentioning
confidence: 99%
“…By inhibition of hydroxy-3-methylglutaryl-CoA (HMG-CoA), reductase statins block the mevalonate pathway and activation of intermediate products involved in cell signaling pathways, such as apoptosis or cell survival. One previous study showed that atorvastatin ameliorated contrast-induced nephropathy and reduced the extent of renal tubular cell apoptosis that is associated with the decreased expression of proapoptotic Bax/caspase-3 and increased Bcl-2 [ 17 ]. Another study that demonstrated the renoprotective effects of pitavastatin on cisplatin-induced AKI pointed to suppression of the mitogen-activated protein kinase (MAPK)/NF-kB/inflammation axis and intrinsic apoptotic pathway [ 18 ].…”
Section: Introductionmentioning
confidence: 99%